Odronextamab, a human CD20×CD3 bispecific antibody in patients with CD20-positive B-cell malignancies (ELM-1): results from the relapsed or refractory non-Hodgkin lymphoma cohort in a single-arm, multicentre, phase 1 trial. Issue 5 (May 2022) - Bannerji, Rajat; Arnason, Jon E; Advani, Ranjana H; Brown, Jennifer R; Allan, John N; Ansell, Stephen M; Barnes, Jeffrey A; O'Brien, Susan M; Chávez, Julio C; Duell, Johannes; Rosenwald, Andreas; Crombie, Jennifer L; et al.
Summary: Background: Odronextamab is a hinge-stabilised, fully human IgG4-based CD20 × CD3 bispecific antibody that binds CD3 on T cells and CD20 on B cells. We aimed to evaluate the safety and antitumour activity of odronextamab in patients with relapsed or refractory B-cell non-Hodgkin lymphoma. Methods: This single-arm, multicentre, phase 1, dose-escalation and dose-expansion (ELM-1) trial was conducted at ten academic sites across the USA and Germany. Patients aged 18 years or older with CD20-positive relapsed or refractory B-cell malignancies who previously received CD20-directed antibody therapy and who had at least one measurable lesion, and an ECOG performance status of 0 or 1 were included. Patients received intravenous odronextamab, according to a step-up dosing schedule in cycle 1, followed by treatment once per week at target doses ranging from 0·1 mg to 320 mg during cycles 2–4 (each cycle was 21 days). After cycle 4, maintenance treatment occurred every 2 weeks until disease progression or unacceptable toxicity. The primary endpoint of safety was assessed by the incidence of adverse events and dose-limiting toxicities to determine the maximum tolerated dose or phase 2 dose of odronextamab, or both. Preliminary antitumour activity, as measured by objective response rate, was a secondary endpoint. This study is registered with ClinicalTrials.gov, NCT02290951 . Findings: From Feb 4, 2015, to Sept 25, 2021, 145 heavily pretreated patients (median of 3 (IQR 2–5] previous therapies) were enrolled (94 to the dose-escalation and 51 to the dose-expansion part of the study). The median age of patients was 67·0 years (IQR 57·0–73·0); 101 (70%) were male and 44 (30%) were female; most participants were White (119 [82%]) and not Hispanic or Latino (132 [91%]). 42 (29%) patients received previous CAR T therapy and 119 (82%) were refractory to the last line of therapy. Median duration of follow-up was 4·2 months (IQR 1·5–11·5). During dose escalation, odronextamab was administered up to the maximum dose of 320 mg once per week and no dose-limiting toxicities were observed. The recommended dose for expansion in patients with follicular lymphoma grade 1–3a was 80 mg and was 160 mg for patients with diffuse large B-cell lymphoma. Cytokine release syndrome and neurological treatment-emergent adverse events were predominantly low grade and did not result in treatment discontinuation. The most common grade 3 or worse treatment-emergent adverse events were anaemia (36 [25%]), lymphopenia (28 [19%]), hypophosphataemia (27 [19%]), neutropenia (27 [19%]), and thrombocytopenia (20 [14%]). Serious treatment-emergent adverse events occurred in 89 (61%) of 145 patients; the most frequent were cytokine release syndrome (41 [28%]), pyrexia (11 [8%]), pneumonia (nine [6%]), and infusion-related reaction (six [4%]). Four deaths were considered related to treatment (gastric perforation in a patient with gastric involvement by lymphoma, lung infection, pneumonia, and tumour-lysis syndrome). Objective response rate was 51% (95% CI 42–59; 72 of 142). In patients with follicular lymphoma who received odronextamab doses of 5 mg or higher, the objective response rate was 91% (95% CI 75–98; 29 of 32) and the complete response rate was 72% (95% CI 53–86; 23 of 32). In patients with diffuse large B-cell lymphoma without previous CAR T-cell therapy who received doses of 80 mg or higher, the objective response rate was 53% (eight of 15) and all responses were complete responses. In patients with diffuse large B-cell lymphoma who had previous CAR T-cell therapy and received doses of 80 mg or higher, the objective response rate was 33% (ten of 30) and complete response rate was 27% (eight of 30). Interpretation: Odronextamab monotherapy showed a manageable safety profile and encouraging preliminary activity, including durable responses in heavily pretreated patients with B-cell non-Hodgkin lymphoma, supporting further clinical investigation in phase 2 and 3 trials. Funding: Regeneron Pharmaceuticals.